Surface-Based Spontaneous Oscillation in Schizophrenia: A Resting-State Functional Magnetic Resonance Imaging Study - Cao, Xianyu; Huang, Huan; Zhang, Bei; Jiang, Yuchao; He, Hui; Duan, Mingjun; Jiang, Sisi; Tan, Ying; Yao, Dezhong; Li, Chao; Luo, Cheng (Frontiers in Human Neuroscience, 2021)
Schizophrenia (SZ) is considered as a self-disorder with disordered local synchronous activation. The previous studies have reported widespread dyssynchrony of local activation in patients with SZ, which may be one of the crucial physiological mechanisms of SZ. To further verify this assumption, the present study used a surface-base two-dimensional regional homogeneity (2dReHo) approach to compare the local neural synchronous spontaneous oscillation between patients with SZ and healthy controls (HC), instead of the volume-based regional homogeneity approach described in previous study. Ninety-seven SZ patients and 126 HC were recruited to this study and we found the SZ showed abnormal 2dReHo across the cortical surface. Specifically, at the global level, the SZ patients showed significantly reduced global 2dReHo; at the vertex level, the foci with increased 2dReHo in SZ were located in the default mode network (DMN), frontoparietal network (FPN) and limbic network (LN), however, foci with decreased 2dReHo were located in the somatomotor network (SMN), auditory network (AN) and visual network (VN). Additionally, the present study found positive correlations between the 2dReHo of bilateral rectus and illness duration, as well as a significant positive correlation between the 2dReHo of right orbital inferior frontal gyrus (OIFG) with the PANSS negative scores in the SZ patients. Therefore, the 2dReHo could provide some effective features contributed to explore the pathophysiology mechanism of SZ.